Merchant Banking - Factors Determining its Shape in India - Singh, Anand (Indian Journal of Finance, 2009)
Today, perhaps, no country can have an isolated existence ignoring the global and international situation. The collapse of socialism in the Soviet Union, declining of communism in the East European countries and economic reforms undertaken by communist China by opening it’s market to the outside world in the name of socialist market economy have influenced India to change it’s Nehru-Ian mixed economic policy to a liberalized economic policy followed by restructuring and reforming of the financial sector. Privatization and Globalization have become watch words today. The Government of India has adopted the new liberalized economic policy from July 1991 and one of the main agendas of the new policy is banking reforms. In this process of reforms the importance of Merchant Banking should not be neglected. The whole banking system in India and abroad is bound to change in the second millennium. Merchant banking cannot be an exception.